PENGARUH BERAT ROLLER CVT (CONTINUOUSLY VARIABLE TRANSMISSION) DAN VARIASI PUTARAN MESIN TERHADAP TORSI PADA YAMAHA MIO SPORTY TAHUN 2007 - Adityas, Priya (Jurnal Nosel, 2012)
The purpose of this research are: (1) To know the effect of CVT (Continuously Variable Transmission) roller weight to torque on Yamaha Mio Sporty 2007, (2) To know the effect of variation of engine rotations to torque on Yamaha Mio Sporty 2007, (3) To know the effect of interaction between CVT (Continuously Variable Transmission) roller weight and variation of engine rotations to torque on Yamaha Mio Sporty 2007. The research used experimental methods and the types of quantitative research. Data of analysis used two-way analysis of variance (Anova), which is the prerequisite tests previously performed tests of normality (Liliefors test) and tests of homogeneity (Bartlett test), then performed multiple comparison tests (Scheffe test) is done. Based the research can conclude that: (1) There are an effect of CVT (Continuously Variable Transmission) roller weight to torque on Yamaha Mio Sporty of 2007. (2) There are an effect of variation of engine rotations to torque on Yamaha Mio Sporty 2007. (3) There are an effect interaction between CVT (continuously variable transmission) roller weight and variation of engine rotations to torque on Yamaha Mio Sporty 2007. Maximum torque is 3.95 N.m, obtained from CVT roller weight 8.5 gr with engine rotations at 6000 RPM.